Can filling phase urodynamic parameters predict the success of the bulbar artificial urinary sphincter in treating post‐prostatectomy incontinence?. Issue 6 (27th September 2016) - Solomon, Eskinder; Veeratterapillay, Rajan; Malde, Sachin; Harding, Christopher; Greenwell, Tamsin Jillian
Abstract : Objective: To evaluate whether filling phase urodynamic parameters can predict the success of the artificial urinary sphincter (AUS) in treating post‐prostatectomy incontinence (PPI). Materials and Methods: We reviewed the pre‐AUS urodynamics of 99 patients with PPI at two tertiary referral centers. We documented the peak DO pressure (Pdet ), capacity, and compliance (C). We defined success as patient‐reported continence or only using one safety pad. Patients' perception of improvement was assessed using the PGI‐I score. Results: Sixty‐eight percent (n = 68) of patients had a successful outcome. The mean compliance for the "success" and "failure" group was 112.3 mL/cmH2 O (±119.7) and 34.1 mL/cmH2 O (±36.2), respectively. Fifty‐five percent (17/31) of patients in the "failure" group demonstrated DO(Pdet  = 36.2 ± 18.2 cmH2 O) compared to 18% (12/68) in the success group. The differences between the two groups in Pdet and compliance were statistically significant (all P  < 0.01). There was, however, no statistical difference between the mean cystometric capacities of patients in the two outcome groups. Thirteen out of 18 (72%) patients who had radiotherapy had a poor outcome ("success" group only 15% [9/59]). These results were used to develop a nomogram for the probability of AUS success. A good inverse correlation ( r  = −0.65) was demonstrated between the probability of AUS success as deduced from the nomogram and PGI‐I score post‐AUS implantation Conclusion: Compliance and Pdet are predictors of outcome following AUS implantation for PPI. We have developed and internally validated a nomogram that may be used to determine an individualized likelihood of AUS success. This nomogram may be used as a counseling tool to objectively set realistic expectations of continence post‐AUS implantation.